Academic analytics: mapeando o genoma da universidade - Ferreira, Sérgio André (2014)
Higher education institutions (HEIs) have multiple technologic subsystems for administrative, pedagogical management and quality purposes, which gather an immense volume of data from various sources and which do not communicate with each other. The domain of the analytic performances in Education emerges from the need to aggregate multiple sources of data, which the complexity of treatment associated with the ease of mobilizing selected information will make it possible to understand reality and optimize management actions. In this article, we present the architecture and results achieved in the development of an Academic Analytics aggregator of multiple sources of data on the educational activity.